Potential benefits of egg white hydrolysate in the prevention of Hg-induced dysfunction in adipose tissue. Issue 11 (16th May 2022) - Rizzetti, Danize Aparecida; Corrales, Patricia; Uranga-Ocio, José Antonio; Medina-Gómez, Gema; Peçanha, Franck Maciel; Vassallo, Dalton Valentim; Miguel, Marta; Wiggers, Giulia Alessandra
Abstract : EWH prevented the morphological and metabolic disorder induced by chronic Hg exposure at low doses, by improving antioxidant defenses, inactivating pro-apoptotic pathways and normalizing the mRNA expression of PPARs and adipokines. Abstract : Aim : To investigate the effects of egg white hydrolysate (EWH) on the lipid and glycemic metabolism disruption in the white adipose tissue (WAT) dysfunction induced by mercury (Hg). Experimental : Wistar rats were treated for 60 days: control (saline, intramuscular – i.m.); hydrolysate (EWH, gavage, 1 g kg −1 day −1 ); mercury (HgCl2, i.m., 1 st dose 4.6 μg kg −1, subsequent doses 0.07 μg kg −1 day −1 ) and hydrolysate-mercury (EWH-HgCl2 ). Hg level and histological analyses were performed in epididymal WAT (eWAT), pancreas and liver. GRP78, CHOP, PPARα, PPARγ, leptin, adiponectin, and CD11 mRNA expressions were analyzed in eWAT. The plasma lipid profile, glucose, and insulin levels were measured. Antioxidant status was also evaluated in the plasma and liver. Results : EWH intake prevented the reduced eWAT weight, adipocyte size, insulin levels, and antioxidant defenses and the increased glucose and triglyceride levels induced by Hg exposure; hepatic glutathione levels were higher in rats co-treated with EWH. The increased mRNA expression of CHOP, PPARα, and leptin induced by Hg was reduced in co-treated rats. EWH did not modify the elevated mRNA expression of GRP78, PPARγ and adiponectin in Hg-treated rats. Increased levels of Hg were found in the liver; the co-treatment did not alter this parameter. EWH prevented the morphological and metabolic disorder induced by Hg, by improving antioxidant defenses, inactivating pro-apoptotic pathways and normalizing the mRNA expression of PPARs and adipokines. Its effects enabled an increase in insulin levels and a normal balance between the fat storage and expenditure mechanisms in WAT. Conclusions : EWH may have potential benefits in the prevention and management of Hg-related metabolic disorders.